2018
DOI: 10.1109/jphotov.2018.2861713
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Vapor-Phase Direct Doping for High-Efficiency Solar Cells

Abstract: An alternative boron emitter diffusion process called rapid vapor-phase direct doping (RVD) is studied and applied to n-type silicon solar cells with a tunnel oxide passivated electron contact (TOPCon). The RVD emitter diffusion process occurs under an atmosphere containing only the dopant gas and hydrogen. Thus, compared with standard tribromide diffusion processes, no oxygen is present. Hence, no boron glasses form during the RVD process. Consequently, a faster diffusion process with fewer chemical treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
4
1
Order By: Relevance
“…Compared to previous results with homogeneous emitters [9] the short circuit current J SC is increased the process temperature lowered, and reflection properties are not affected by flattened pyramids. However, previous cells had a higher open circuit voltage V OC of 703 mV and a FF of 82.8%.…”
Section: Solar Cellscontrasting
confidence: 75%
See 2 more Smart Citations
“…Compared to previous results with homogeneous emitters [9] the short circuit current J SC is increased the process temperature lowered, and reflection properties are not affected by flattened pyramids. However, previous cells had a higher open circuit voltage V OC of 703 mV and a FF of 82.8%.…”
Section: Solar Cellscontrasting
confidence: 75%
“…n-type TOPCon cells with B-RVD emitters as schematically shown in Fig. 1 were already successfully realized using a sequential process with emitter diffusion on the front side prior to the TOPCon processes on the rear side [9]. These cells reached a high efficiency of up to 23.9% for a homogeneous emitter diffused at 1030 °C, which demonstrates the potential of RVD.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…The same apparatus that is used for the fabrication of PERC solar cells can also be used for manufacturing the TOPCon structure. 21,22 The manufacturing of the TOPCon structure is more straightforward than that of the PERC solar cells, as there is complete passivation and metal contact at the rear side. During the fabrication route of TOPCon devices, thin layers of tunnel oxide and highly doped polycrystalline-silicon (poly-Si) are deposited, effectively minimizing the charge carrier recombination.…”
Section: Introductionmentioning
confidence: 99%
“…A TOPCon solar cell is uniform with rear cell structure, providing 1D carrier transport and carrier-selective contact, and therefore, high V OC (open-circuit voltage) and FF. Previous works on TOPCon solar cells, involving both experimental and theoretical aspects, were mainly studies of process developments aimed at cell fabrication: evaluations of substrate temperature using plasma-grown tunnel oxide 13) and passivation quality with annealing temperature, 14) comparison of oxidation processes for growing tunnel oxide with passivation quality and contact resistivity, 15) recombination analysis using numerical simulation, 16) application of rapid vaporphase direct doping process to TOPCon solar cells, 17) TOPCon solar cell process using ion implantation and evaluation of process conditions, 18) and demonstrations of multi-crystalline n-type TOPCon solar cell with recombination, lifetime mapping, and comparison of manufacturing processes. 19) Choi et al reported the refined TOPCon solar cell structure combined with amorphous silicon.…”
Section: Introductionmentioning
confidence: 99%